Pengaruh Batuan Alami Dalam Agregat KasarPada Hrs Terhadap Sifat MarshallDan Nilai Struktural - Arifiyanto, Agus; , Ir. Agus Riyanto, M.T (2017)
Aggregate be one of the factors that affect the quality of pavement mixture. The problem comes when the processing of large boulder to become coarse aggregate, not infrequently there are natural rocks which did not split when solving process. In addition to the current process of solving, natural stones can also be mixed with accidentally when accumulation in Asphalt Mixing Plan. The purpose of this study to determine the effect of natural rocks in a pavement mixture, and the maximum limit of natural rocks that can be tolerated for mixed as rude aggregate. In this study using hot mix asphalt testing (Hot Mix) by Marshall method and calculation of structural value. Marshall Testing Phase I for determine the value of Optimum Asphalt Content (KAO) with bitumen content variation is, 5,5%; 6,0%; 6,5%; 7,0%; 7,5%; 8,0% were then evaluated by the value of Marshall Stability, Flow, VMA, VIM, VFWA and Marshall Quotient. The testing of Marshall Phase II is to test 5 variation of natural rocks content as much as 0%; 5%; 10%; 15%; 20% of the total coarse aggregate use Optimum Asphalt Content, continued to evaluate the value of Marshall Stability, Flow, VMA, VIM, VFWA, and Marshall Quotient to obtain the result of Marshall characteristics in the pavement mixture. And calculating the value of structural with variation speed of vehicle assumed is 5km/h; 10km/h; 15km/h. The results showed that the mixing of natural rocks into pavement mix as a coarse aggregate resulted in the Marshall characteristic value and the structural value of the HRS-Base gradation gradient decreasing. In Marshall's characteristic the maximum 14.6% of natural rocks are found, at a VIM limit that meets the specification of 14.6%, while for others Marshall Properties meets specifications into 20% natural rocks content. The result of Structural Value analysis obtained per variation of natural rocks are: 0,239; 0.229; 0.229; 0.224, and 0,224.